Blockchain Technology for Islamic Marriage Certificate - Elysha Kamaruzaman, Nor; Mohd Yassin, Ihsan; Zabidi, Azlee; Hafizhelmi Kamaru Zaman, Fadhlan; Ismael Rizman, Zairi; Baharom, Rahimi; Abdul Wahab, Norfishah (International Journal of Engineering and Technology, 2018)
In recent years, an individual under the pseudonym of Satoshi Nakamoto devised a revolutionary technology called blockchain as the engine behind the first decentralized virtual currency called Bitcoin. A radical concept departing from government-centric controlled currencies, Bitcoin has emerged as a disruptive technology with the power to revolutionize business and its processes. Advantages of the blockchain include decentralized control, immutability, elimination of central authority and solution of concurrency problems in traditional databases. Leveraging on the advantages of blockchain technology defined above, this paper discusses the potential application of blockchain technology for storage of Islamic marriage certificates. Marriage certificates are documents issued to couples to legally recognize their marriage. Due to its paper-based nature, there is significant risk for them to be forged or frauded. These issues can be addressed effective using blockchain. The proposed application was implemented using smart contracts on a simulated Ethereum platform. A smart contract is designed to execute automatically under certain predefined conditions. The use of smart contracts eliminate manipulation by a single party. In addition, the immutable concept of blockchain ensures that data integrity is always preserved, greatly reducing the risk of fraud.Â Â